2013
DOI: 10.5194/hess-17-1133-2013
|View full text |Cite
|
Sign up to set email alerts
|

A generalized Damköhler number for classifying material processing in hydrological systems

Abstract: Abstract. Assessing the potential for transfer of pollutants and nutrients across catchments is of primary importance under changing land use and climate. Over the past decade the connectivity/disconnectivity dynamic of a catchment has been related to its potential to export material; however, we continue to use multiple definitions of connectivity, and most have focused strongly on physical (hydrological or hydraulic) connectivity. In contrast, this paper constantly focuses on the dynamic balance between tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 55 publications
2
87
0
Order By: Relevance
“…Therefore, we are left with a paradox: multiscale and cross biome understanding is needed but comprehensive study of the different processes involved in riparian nitrogen cycling is only feasible at relatively small plot scales. Indeed, so far, the evaluation of the buffering capacity of riparian zones has focused on very detailed, small-scale hydrological and biogeochemical assessments, which revealed that removal capacity is intrinsically dependent on the ratio between the residence time of nitrate in the riparian zone and the denitrification rate (i.e., the Damköhler ratio; Sabater et al, 2003;Ocampo et al, 2006;Oldham et al, 2013;Pinay et al, 2015). Yet, simply examining the variability of a particular process (e.g., denitrification) at relatively small scales does not adequately quantify the potential of riparian corridors to buffer nitrogen inputs or supply nitrogen to stream food webs at catchment scale.…”
Section: Riparian Corridors Function As Kidneys Of River Systemsmentioning
confidence: 99%
“…Therefore, we are left with a paradox: multiscale and cross biome understanding is needed but comprehensive study of the different processes involved in riparian nitrogen cycling is only feasible at relatively small plot scales. Indeed, so far, the evaluation of the buffering capacity of riparian zones has focused on very detailed, small-scale hydrological and biogeochemical assessments, which revealed that removal capacity is intrinsically dependent on the ratio between the residence time of nitrate in the riparian zone and the denitrification rate (i.e., the Damköhler ratio; Sabater et al, 2003;Ocampo et al, 2006;Oldham et al, 2013;Pinay et al, 2015). Yet, simply examining the variability of a particular process (e.g., denitrification) at relatively small scales does not adequately quantify the potential of riparian corridors to buffer nitrogen inputs or supply nitrogen to stream food webs at catchment scale.…”
Section: Riparian Corridors Function As Kidneys Of River Systemsmentioning
confidence: 99%
“…Approximations that neglect unsaturated flow have often been used for analysing water movement beneath the ground (Brutsaert, 2005), but the results from CB1 suggest that such an approximation should be rejected here because it is not fixed whether the saturated or the unsaturated flow has the larger effect on stormflow responses. The important role of hydrologic or hydraulic connectivity in catchment processes has already been discussed elsewhere (Michaelides and Chappell, 2009;Oldham et al, 2013), and HC, efficiently connecting the unsaturated and saturated flows, will be used as a key concept for the flow responses in this paper.…”
Section: Stormflow Observations In Catchments With Fixed Contributionmentioning
confidence: 99%
“…We propose that the comparison of travel time from catchments from differing biomes could lead to a more systematic understanding of catchment behaviour and general theory. Because biogeochemistry is tightly linked to residence time, a better understanding of the travel time distributions will improve the assessment of nutrient removal capacity (Pinay et al, 2015), climate change impacts on stream chemistry (Abbott et al, 2015;Goode, 1996;McGuire et al, 2005) and exposure time (Ginn, 1999;Frei et al, this issue;Oldham et al, 2013).…”
Section: Temporal Variabilitymentioning
confidence: 99%
“…These hydrological parameters influence catchment biogeochemistry (Ocampo et al, 2006;Oldham et al, 2013;Pinay et al, 2015;Tetzlaff et al, 2007), further increasing their value as 4 indicators and predictors of catchment-scale water quality and chemistry. Because these parameters are of great general interest they feature prominently in the inputs and outputs of many models (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation